Water Quality Assessment of The Three Lakes of Barandabhar Forest Corridor, Central Nepal - Acharya, Keshab; Sharma, Bimala; Dhakal, Aradhana (Saptagandaki Journal, 2023)
Addressing the global challenge of securing water for both human needs and ecosystem health is crucial. This study aims to characterize the physiochemical parameters of three lakes in the Bharandabhar forest corridor, Chitwan, Central Nepal: Tiger Lake, Kalimati Lake, and Rhino Lake. During the pre-monsoon season, four different sites (Eastern, Western, Northern, and Southern) of each lake were examined. To ensure precision, five replicated water samples were collected from each site, and standard protocols were applied to analyze various physiochemical parameters, such as pH, temperature, dissolved oxygen, free carbon dioxide, total hardness, chloride, total alkalinity, conductivity, nitrate, inorganic phosphorus, and total solid matter. Also, the Water Quality Index (WQI) was calculated. Results show that physiochemical parameter values mostly align with permissible limits according to regional and international guidelines. However, the mean phosphorous concentration and pH values of Tiger and Kalimati lakes exceed these limits. Rhino Lake displayed a mildly alkaline pH, while Kalimati and Tiger lakes exhibited slightly acidic characteristics. An interesting observation is the significant negative correlation between temperature and dissolved oxygen, indicating that as temperature rises, dissolved oxygen levels decrease. Additionally, WQI suggests that all three lakes maintain good water quality. However, a concerning finding is that all three lakes exhibited hyper-eutrophic conditions based on their phosphorous concentration. The lakes face significant threats due to high levels of organic pollutants and a rapid eutrophication process. Authorities must take significant actions to safeguard the lakes and ensure their future well-being. This research highlights the urgent need for environmental protection and conservation efforts to preserve the water quality and ecological balance of the Bharandabhar forest corridor lakes for the well-being of both human communities and the ecosystem.